Multiuser hybrid analogue/digital beamforming for massive multiple-input–multiple-output - Wu, Keying; Wu, Lu; Zhang, Jianwen (IET communications, 2016)
The authors propose a generalised multi-layer architecture for the phase shifter network (PSN) in hybrid analogue/digital beamforming (BF), which provides flexible trade-offs between the performance and implementation complexity. By changing the layer number, the authors can adjust the complexity of the PSN and the achievable performance. A two-stage BF algorithm is adopted, in which the analogue and digital BF matrices are designed separately. Analogue BF is adaptive to the second-order channel statistics. A simple iterative algorithm is proposed to maximise an upper bound of the average rate of the effective channel after analogue BF. Digital BF is adaptive to the effective channel for multiuser interference cancellation. Both ideal phase shifters and discrete phase shifters with limited phase and amplitude resolutions are considered in the algorithm design. Theoretical analysis and simulation are used to demonstrate the good performance and flexibility of the proposed technique. In a 64-antenna system, it can use 16 radio-frequency chains to perform very closely to full digital BF with a fully-connected PSN, or achieve 70–80% performance with a simple PSN. It is also robust against the limited phase shifter resolution. It enables us to select the proper performance and implementation complexity according to the requirement and capability of real systems.